2011
DOI: 10.1021/jp200843s
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio QM/MM Free-Energy Studies of Arginine Deiminase Catalysis: The Protonation State of the Cys Nucleophile

Abstract: The first step of the hydrolytic deimination of L-arginine catalyzed by arginine deiminase is examined using ab initio quantum mechanical/molecular mechanical molecular dynamics simulations. Two possible protonation states of the nucleophilic Cys406 residue were investigated and the corresponding activation free energies were obtained via umbrella sampling. Our calculations indicated a reaction free-energy barrier of 21.3 kcal/mol for the neutral cysteine, which is in reasonably good agreement with the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Finally, 10 ns MD simulation for equilibration was performed. [51][52][53][54][55][56][57][58][59][60] As for the MM subsystem, the Amber99SB force field [35][36][37] was employed as in the above classical MD simulations. The Langevin method was utilized to control the temperature at 300 K. The bonds involving hydrogen atoms were constrained by using the SHAKE scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 10 ns MD simulation for equilibration was performed. [51][52][53][54][55][56][57][58][59][60] As for the MM subsystem, the Amber99SB force field [35][36][37] was employed as in the above classical MD simulations. The Langevin method was utilized to control the temperature at 300 K. The bonds involving hydrogen atoms were constrained by using the SHAKE scheme.…”
Section: Methodsmentioning
confidence: 99%
“…further explored the inhibition mechanism of PAD4 by F‐amidine and the protonation state of active site cysteine . They found that the cysteine and histidine exist as a thiolate–imidazolium ion pair, which was inconsistent with the results of Ke et al . In addition, study of ADI enzyme supports the ionic state of active site .…”
Section: Introductionmentioning
confidence: 87%
“…For example, in the proposed deamination mechanism, the three enzymes (PPAD, PAD4 and ADI) employ the same mechanism. However, the active site of PPAD is clearly different from PAD4 and ADI . And during the hydrolysis stage of PPAD, D238 residue was supposed to only play a role in enhancing the nucleophilic ability of hydrolytic water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Berendsen thermostat 40 was used to control the system temperature at 300 K. The final PMF was calculated with the weighted histogram analysis method (WHAM). 41 The QM/MM method used here is essentially the same as in our recent publication on arginine deiminase, 42 which is a member of the same enzyme superfamily as DDAH and is believed to have a similar catalytic mechanism. 43,44 …”
Section: Methodsmentioning
confidence: 99%